Cultural diversity management of children belonging to socially vulnerable families: The voice of families as an axis for innovation in socio-educational intervention - Palasí, Eva; Morata, Txus; Giralt, Pere-Joan; Rocha, Joan Andreu (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2022)
Socio-Educational Centres that work with children and families in risk of poverty and social exclusion and are based in territories with a high index of migrant population favour an upturn of the personal resources of children and families that participate in the activities of such Centres, and in a networking process that favours social cohesion. The families of 6 Socio-Education Centres of Barcelona (N=42) offer their vision about the social contribution of such Centres in order to empower social cohesion in their main territories through an ad hoc questionnaire.